“Constant Communication”: Rural Principals' Leadership Practices During a Global Pandemic - Hayes, Sonya D.; Flowers, Jamon; Williams, Sheneka M. (Frontiers in Education, 2021)
Rural school leaders are met with serious challenges and opportunities to lead rural schools in times of normalcy, but these challenges are amplified during a crisis. Rural school principals in the United States faced an unprecedented crisis when school buildings closed in spring 2020 due to the COVID-19 pandemic. The measure of rural school principals and their response to this crisis is exemplified through their leadership practices. Through qualitative methods, we examined the leadership practices of rural principals through the initial months of the COVID-19 pandemic and quarantine, and we found that rural principals exhibit the practices of caretaker leadership. From the findings, we used a meta-leadership frame to discuss the caretaker leadership practices of rural school principals.